(untitled) (Global Journal of Management and Business Research, 2014)
Employee turnover is an endemic issue in hospitality industry, worldwide. Employee turnover intention acts as a proxy for actual employee turnover. One of the challenging issues faced by the hospitality organizations today is to manage the changing employment relationship. Being in customer service business, hospitality industry capitalizes heavily on its human resources in order to achieve its competitive advantage. Choi and Dickson (2009) emphasized that the hospitality industry is a highly guest service#x2013;oriented business where encounters between employees and guests determine the success of the business.